Microbiome Understanding in Maternity Study (MUMS), an Australian prospective longitudinal cohort study of maternal and infant microbiota: study protocol - Amanda Henry; Emad M El-Omar; Lynne M Roberts; Georgina L Hold; Maria E Craig; Katie Harris; Daniella Susic; Gregory Davis; Anthony J O' Sullivan; Emily McGovern; George Mangos (BMJ Open)
Introduction Pregnancy induces significant physiological and cardiometabolic changes, and is associated with alterations in the maternal microbiota. Increasing rates of prepregnancy obesity, metabolic abnormalities and reduced physical activity, all impact negatively on the microbiota causing an imbalance between the commensal microorganisms (termed dysbiosis), which may drive complications, such as gestational diabetes or hypertensive disorders. Considerable work is needed to define the inter-relationships between the microbiome, nutrition, physical activity and pregnancy outcomes. The role of the microbiota during pregnancy remains unclear. The aim of the study is to define microbiota signatures longitudinally throughout pregnancy and the first year post birth, and to identify key clinical and environmental variables that shape the female microbiota profile during and following pregnancy.Methods and analysis The Microbiome Understanding in Maternity Study (MUMS) is an Australian prospective longitudinal cohort study involving 100 mother–infant pairs. Women are enrolled in their first trimester and followed longitudinally. Assessment occurs at <13+0, 20+0–24+6 and 32+0–36+6 weeks gestation, birth and 6 weeks, 6 months and 12 months postpartum. At each assessment, self-collected oral, vaginal and faecal samples are collected with an additional postpartum skin swab and breastmilk sample. Each infant will have oral, faecal and skin swab samples collected. Measurements include anthropometrics, body composition, blood pressure, serum hormonal and metabolic parameters and vaginal pH. Dietary intake, physical activity and psychological state will be assessed using validated self-report questionnaires, and pregnancy and infant outcomes recorded. Parametric and non-parametric hypothesis tests will be used to test the association between high-risk and low-risk pregnancies and their outcomes.Ethics and dissemination The study received the following approval: South Eastern Sydney Local Health District Research Ethics Committee (17/293 (HREC/17/POWH/605). Results will be made available to the participants of MUMS, their families and the funding bodies; in the form of a summary document. Results for the greater maternity care community and other researchers will be disseminated through conferences, local, national and international presentations and peer-reviewed publications.Trial registration number ACTRN12618000471280 (prospectively registered).